(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
The goal of this experiment was to compare the effectiveness of three popular synchronization protocols, viz. ovsynch, double prostaglandin (PGF2? /PG) injections, and MAP (Medroxyprogesterone acetate) sponges, in anestrous goats. Twenty one non pregnant multiparous anestrous goats with an average body condition score (BCS = 2.5) were selected. After the last PG injection, all the goats were exposed to three fertile bucks. They were observed to be in standing estrus. For further confirmation of copulation, a vaginal cytology test was performed for the presence of sperm inside the vaginal smear. Serum estradiol (E2) peaks were also estimated by using radioimmunoassay in estrus goats. MAP sponge efficiency with respect to estrus induction was found to be superior (57%) as compared to the rest (Ovsynch14 and PG 0%) (p< 0.05). Post PG standing estrus time in ovsynch and MAP groups was recorded as 48 h and 44 ± 12 h, respectively. The double PG group totally failed to show standing estrus. E2 peak levels ranging from 11-38 pg/ml in ovsynch and 10–25 pg/ml in the MAP group were observed in estrus goats. This study found the MAP sponge protocol most efficient for inducing estrus in anestrous goats.